"But One Needs to Work!": Neoliberal Citizenship, Work‐Based Immigrant Integration, and Post‐Socialist Subjectivities in Berlin‐Marzahn. Issue 4 (12th October 2012) - Matejskova, Tatiana
Abstract : This paper examines how middle‐aged and older post‐Soviet immigrants in eastern Berlin navigate the neoliberalized landscape of work‐based integration in face of their long‐term unemployment. I first show how these immigrants' own insistence on the centrality of paid work for their feeling integrated contributes to their experience of collective despondency and enrollment in exploitative quasi‐markets, including workfare. Focusing on this insistence, I examine how it draws strength primarily from their continued subscription to the conceptions of self as deeply socially embedded, and of work as a practice of such an embedding, adopted through their Soviet‐era socialization into the culture of dispersed personhood and obligation to work, rather than from their adoption of neoliberal concepts of citizenship in Germany. Contributing to geographies of post‐socialist experience of neoliberalized regimes of citizenship and immigrant integration, this paper thus highlights how some of the aspects of post‐socialist subjectivities dovetail unexpectedly with the neoliberal project.